Effect of co-doped sno2 nanoparticles on photoluminescence of cu-doped potassium lithium borate glass - Namma, Haydar Aboud (2012)
The co-doped SnO2 nanoparticles of lithium potassium borate doped with Cu glass were prepared using the chemical quenching technique. The X-ray diffraction analysis revealed the amorphous nature of the sample. The morphology was determined using high resolution scanning electron microscopy (FE-SEM). The photoluminescence properties and energy band gaps of the glass were investigated. The changes in the energy band gap were due to the concentration of SnO2 nanoparticles and copper ions. An enhancement of almost three times was shown when SnO2 nanoparticles were added as co-dopants to 0.1 mol% of Cu and the peak shapes shifted from blue luminescence to blue and green luminescence.